2020
DOI: 10.3390/jcm9020332
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of Consensus-Recommended Platelet Function Tests to Assess P2Y12 Inhibition—Insights for Multi-Center Trials

Abstract: The vasodilator-associated stimulated phosphoprotein (VASP) phosphorylation level is a highly specific method to assess P2Y12 receptor inhibition. Traditionally, VASP phosphorylation is analyzed by flow cytometry, which is laborious and restricted to specialized laboratories. Recently, a simple ELISA kit has been commercialized. The primary objective of this study was to compare the performance of VASP assessment by ELISA and flow cytometry in relation to functional platelet aggregation testing by Multiplate® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…2 B). Bélanger et al reported that ARC-66096 (10 µM) significantly inhibits platelet aggregation [ 19 ], and Quintas et al demonstrated that ARC-66096 (10 µM) can significantly abrogate adenosine 5ʹ- O -(2-thio)-diphosphate-induced astroglial proliferation [ 20 ], thus indicating 10 µM to be the optimal concentration of ARC-66096 for antagonizing ADP-activated P2Y 12 signaling. Notably, we established that the P2Y 13 antagonist MRS2211 (50–100 µM) significantly abrogated the ADP-promoted expression of MCP-1/CCL2 in a concentration-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 B). Bélanger et al reported that ARC-66096 (10 µM) significantly inhibits platelet aggregation [ 19 ], and Quintas et al demonstrated that ARC-66096 (10 µM) can significantly abrogate adenosine 5ʹ- O -(2-thio)-diphosphate-induced astroglial proliferation [ 20 ], thus indicating 10 µM to be the optimal concentration of ARC-66096 for antagonizing ADP-activated P2Y 12 signaling. Notably, we established that the P2Y 13 antagonist MRS2211 (50–100 µM) significantly abrogated the ADP-promoted expression of MCP-1/CCL2 in a concentration-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2B). Bélanger et al reported that ARC-66096 (10 µM) signi cantly inhibits platelet aggregation [19], and Quintas et al demonstrated that ARC-66096 (10 µM) can signi cantly abrogate adenosine 5 -O-(2-thio)-diphosphate-induced astroglial proliferation [20], thus indicating 10 µM to be the optimal concentration of ARC-66096 for antagonizing ADP-activated P2Y 12 signaling. Notably, we established that the P2Y 13 antagonist MRS2211 (50-100 µM) signi cantly abrogated the ADP-promoted expression of MCP-1/CCL2 in a concentration-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The VASP assay was performed according to the manufacturer’s instructions (Diagnostica Stago S.A.S.) [ 8 ]. Results were obtained by flow cytometry and expressed as platelet reactivity index (PRI).…”
Section: Methodsmentioning
confidence: 99%